The Conceptualization of Education Policy: History, Theory and Internship. (Journal of Educational Sciences, 2016)
The article reveals the historical and theoretical background for the conceptualization of educational policy. Presents an analysis of fundamental works devoted to investigation of a system of bases of modeling education strategy (F. Coombes, B. Gershunsky, A. Nurmagambetov, A. Kusainov, A. Bulatbayeva and others). The definitionof the conceptualization of education policy as a way of understanding the positions of the theory of pedagogical concepts. Classification of concepts in the field of educational policy. Requirements are considered models of met concept. In practice, implementation of the educational policy considered strategy online educational organization (route-perspective – program – method – landmark – concretization) routing education organization (updated content, teaching methods, methods of organization of a holistic educational process). Use in the design process and route build the content of education in secondary school heuristic learning promoted innovative updating of educational content, its partial integration and restructuring. The article was prepared in the framework of the project of the Ministry of education and science of the Republic of Kazakhstan «the Study of educational policy of Kazakhstan and countries of Europe: comparative aspect for the development of human capital and the formation of an intellectual nation».
Keywords: education policy; conceptualization; strategy; system analysis